Penanaman Nilai Akhlak Kepada Sesama Melalui Shalat Berjamaah - Silvia, Silvia; Ikhlas, Al (An-Nuha, 2023)
Morals to others is something that must be instilled in students starting from an early age because it is very important in carrying out daily activities with fellow living beings. This study aims to determine how the stages of instilling moral values in others through congregational prayer in students. This research uses a qualitative method with a descriptive approach. Data was taken through observation, interviews, and documentation with 4 informants, namely one pai teacher, one homeroom teacher, and two students. The results of the research on the cultivation of moral values to others are the first three stages, namely value transformation, value transactions, and value internalization. At the value transformation stage the teacher uses the question and answer method, discussion and lecture method, while at the value transaction stage the teacher uses several methods, namely the habituation method, conversation method, promise and threat method and the last stage, namely the internalization stage, the teacher instills value using the exemplary method and reward and punishment. And the conclusion of this study is that in instilling moral values to others through congregational prayer there are three stages, namely the value transformation, value transaction and internalization stages.